The importance of environment on respiratory genotype/phenotype relationships in the Inuit - Candelaria, P.; Backer, V.; Khoo, S.; Bizzintino, J.; Hayden, C.; Baynam, G.; Laing, I.; Zhang, Guicheng; Porsbjerg, C.; Goldblatt, J.; Le Souëf, P. (2010)
Background: Genetic and environmental influences and their interactions are central to asthma pathogenesis. This study aimed to investigate the effects of different macro-environments on asthma genotype-phenotype associations in two geographically separated populations with common ancestry. Methods: To accomplish this, two unselected populations of Inuit were recruited, one living in Greenland (n = 618) and the other in Denmark (n = 739). Subjects were genotyped for CD14 C-159T, SCGB1A1 A38G, ADRB2 Arg16Gly and Gln27Glu. The resulting genetic data were analysed for relationships with asthma-related parameters including lung function, ever asthma, atopy, rhinitis and dermatitis. Results: The results showed contrasting magnitude and direction of genetic associations between the two geographically separate Inuit populations. In Greenland, the ADRB2 16Arg allele was associated with male-specific lower lung function, but in Denmark the same allele was associated with male-specific higher lung function. This allele was also associated with higher incidence of ever asthma in Denmark but not in Greenland. The SCGB1A1 38A allele was associated with lower rhinitis prevalence in Greenland but not in Denmark. Conclusions: These associations suggest that environment interacts with candidate asthma genes to modulate asthma pathogenesis in the Inuit. © 2009 John Wiley & Sons A/S.